REMONOR : résultats 2005. Evaluation de la mortalité, croissance et qualité des huîtres creuses - Mary, Charlotte; Pien, S; Blin, J.l.; Ropert, Michel (2006)
The regional monitoring network REMONOR, relying on the experience of IFREMER's REMORA national network, each year assesses the mortality, growth and quality for two age classes ("adults" = 2 years and "juveniles" = 1 year) of cup oysters, distributed among various farm sites in the main oyster farming sectors of Lower Normandy. This network, led in collaboration by LERN (Environment Resources Laboratory) and SMEL (Coastline Installations Public-Private Entity), this year welcomes a new farm site in Veules les Roses, in Seine Maritime (76), bringing to 18 the total number of monitored sites. For operational reasons, a reduced monitoring protocol was conducted in 2005 on this last farm site, which will not take on the network's standardised protocol until 2006. It is subject to processing and partial analysis for this first year. The number of mortalities observed in 2005 is low and confirms the trend noted since 2002. The regional averages are in fact 6.6% for the adults and 7.7% for the juveniles. With the exception of the juveniles in North Gouville (CO07), whose mortality is probably random, no rate was higher than 12%. A contrario, overall growth is not good, with an average individual weight in December of 58g for the adults. This trend mainly affects the whole of the West Coast of Cotentin (with the exception of Chausey). For the juveniles, the average individual weight in December is slightly lower than the average recorded since 1998. It is in Calvados (Bay of Les Veys and Meuvaines) that the growth deficits are the most significant for this age class. On a qualitative level, the AFNOR index is, in the whole of the region, lower than the average over several years (10.7 in 2005 against 11.5 since 1993). This reduction of quality is especially noticeable on the Cotentin east coast and in the Bay of Les Veys. The results concerning the infestations by Polydora are, however, excellent and 2005 is proving itself to be the best year since REMONOR's beginning because of the low levels of infestation observed. ...